2009
DOI: 10.1021/jp909118c
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Charge Carrier Relaxation and Charge Transfer Dynamics of CdTe/CdS Core−Shell Quantum Dots as Studied by Femtosecond Transient Absorption Spectroscopy

Abstract: We are reporting ultrafast charge carrier and charge transfer dynamics of the CdTe quantum dot (QD) and type II CdTe/CdS core-shell QD materials with different shell (CdS) thicknesses. Herein, we have synthesized CdTe and CdTe/CdS core-shell quantum dots by using 3-mercaptopropionic acid as a capping agent. Steady state absorption and emission studies confirmed successful synthesis of CdTe QD and CdTe/CdS core-shell QD materials. Time-resolved emission studies indicate a longer emission lifetime of the CdTe/Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(141 citation statements)
references
References 55 publications
11
130
0
Order By: Relevance
“…S9. This is presumably due to contributions from 25 more than one species. It was found that the decay phenomena were similar over the energy range 5-100 nJ (data recorded at 100 nJ excitation are also supplied in the see ESI Fig.…”
Section: Picosecond Transient Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…S9. This is presumably due to contributions from 25 more than one species. It was found that the decay phenomena were similar over the energy range 5-100 nJ (data recorded at 100 nJ excitation are also supplied in the see ESI Fig.…”
Section: Picosecond Transient Absorptionmentioning
confidence: 99%
“…1 The II-VI metal chalcogenides such 20 as ZnS, CdS, CdSe, CdTe, PbSe, and PbTe have been extensively studied and their variable direct band gap and resultant tuneable photoluminescence has led to numerous applications including photodynamic therapy, imaging and sensing applications. [2][3][4][5][6][7][8][9][10][11] Of particular interest is the use of quantum dots as acceptor/donor 25 components for the conversion of light energy into electricity in a photovoltaic device. [12][13][14][15][16] A significant obstacle to the development of high-performance photovoltaic cells is the effective separation of photogenerated electron-hole pairs and the transfer of the electrons to the electrode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, two strategies, ice bath method 28 and the H 2 Te gas route, 29 were used to prepare fresh Te precursor. However, the ice bath method is time-consuming, usually taking over 6 h, and the H 2 Te gas route is laborious.…”
Section: Synthesis Of Nahtementioning
confidence: 99%
“…To better understand the underlying dynamics and interpret the observed ultrafast kinetics, control TA experiments with electron and hole quenchers [44,236] were also performed. Benzoquinone (BQ) was added into the solution to quench electrons in photoexcited CdSe SCNCs.…”
Section: Data Analysis and Exciton Dynamicsmentioning
confidence: 99%